Integral Design of an Agrivoltaics Research System in Northern Minas Gerais, Brazil - Frederik Schönberger; Ana Valentina Puentes; David Jung; Polyanna Mara de Oliveira (AgriVoltaics Conference Proceedings)
This study aims to derive conceptual agrivoltaic (AV) designs for the first AV research pilot in Minas Gerais Brazil by applying a Key Performance Indicator (KPI) based evaluation method. A selected AV design is assessed regarding its shading characteristics in various scenarios using raytracing algorithms in Python based on the Solstice software. The proposed Elevated AV system demonstrates the best performance respecting the project specific objectives. For the respective design we vary row distances in three scenarios, enabling regression analysis to relate the annual average shading rate to the row pitch. The analysis reveals that for a 30% shading rate, a 3.2 m row distance is required, which is finally recommended to respect the rather sun-loving crop types. Through a border effect analysis, we conclude the necessity of implementing a total AV pilot area of approximately 700 m² to conduct agricultural experiments on 300 m² without edge effects. In general, we highlight the importance of precise AV system design for optimizing agricultural and photovoltaic (PV) performance.